Amaryllidaceae Alkaloids of Belladine-Type from Narcissus pseudonarcissus cv. Carlton as New Selective Inhibitors of Butyrylcholinesterase - Al Mamun, Abdullah; Maříková, Jana; Hulcová, Daniela; Janoušek, Jiří; Šafratová, Marcela; Nováková, Lucie; Kučera, Tomáš; Hrabinová, Martina; Kuneš, Jiří; Korábečný, Jan; Cahlíková, Lucie (Biomolecules, 2020)
Thirteen known (1-12 and 16) and three previously undescribed Amaryllidaceae alkaloids of belladine structural type, named carltonine A-C (13-15), were isolated from bulbs of Narcissus pseudonarcissus cv. Carlton (Amaryllidaceae) by standard chromatographic methods. Compounds isolated in sufficient amounts, and not tested previously, were evaluated for their in vitro acetylcholinesterase (AChE; E.C. 3.1.1.7), butyrylcholinesterase (BuChE; E.C. 3.1.1.8) and prolyl oligopeptidase (POP; E.C. 3.4.21.26) inhibition activities. Significant human BuChE (hBUChE) inhibitory activity was demonstrated by newly described alkaloids carltonine A (13) and carltonine B (14) with IC50 values of 913 ± 20 nM and 31 ± 1 nM, respectively. Both compounds displayed a selective inhibition pattern for hBuChE with an outstanding selectivity profile over AChE inhibition, higher than 100. The in vitro data were further supported by in silico studies of the active alkaloids 13 and 14 in the active site of hBuChE.
Keywords: Protein Binding; cholinesterasové inhibitory; Narcissus; Molecular Docking Simulation; Alkaloids; Humans; alkaloidy; butyrylcholinesterasa; vazebná místa; lidé; Butyrylcholinesterase; simulace molekulového dockingu; Cholinesterase Inhibitors; Binding Sites; vazba proteinů